The potential role of integrin alpha 6 in human mesenchymal stem cells - Al-Obaide, Mohammed; Ishmakej, Albi; Brown, Christina; Mazzella, Matteo; Agosta, Patrina; Perez-Cruet, Mick; Chaudhry, G. Rasul (Frontiers in Genetics, 2022)
Human mesenchymal stem cells (MSCs) are isolated from various adult and perinatal tissues. Although mesenchymal stem cells from multiple sources exhibit similar morphology and cell surface markers, they differ in their properties. In this study, we determined that the expression of integrin alpha 6 (ITGA6) and ITGA6 antisense RNA (ITGA6-AS1) correlates with the proliferation, cell size, and differentiation potential. The expression of ITGA6 was inversely correlated with ITGA6-AS1 in MSCs. The expression of ITGA6 was higher, but ITGA6-AS1 was lower in MSCs from cord placenta junction, cord tissue, and Wharton’s jelly. In contrast, ITGA6 expression was lower, while ITGA6-AS1 was higher in MSCs from the placenta. The bioinformatic analysis showed that ITGA6 genomic DNA transcribes ITGA6-AS1 from the reverse strand, overlapping ITGA6 exon-2. Additionally, we identify several putative promoters (P1-P10) of ITGA6. ITGA6-P10 is CG rich and contains CGI. EMBOSS Cpgplot software revealed a CGI length of 180 bp that extends from nucleotide 125 to 304 of the P10 sequence. We suggest that the post-transcriptional regulation of the ITGA6 in mesenchymal stem cells is controlled by the ITGA6-AS1, which could be a critical factor responsible for the heterogeneity in function and cell fate of human MSCs. These results may provide further impetus for investigations to unravel the mechanisms of ITGA6 regulation that could help maintain or improve the properties of mesenchymal stem cells.